Driving Sustainable Supply Chains: Blockchain-enabled Eco-efficiency for Resilient Customs Ports - Ahmad Moh’D Ababneh; Manal Ali Almarashdah; Iqbal Jebril; Murad Ali Ahmad Al-Zaqeba; Nasser Assaf (Growing Science Ltd, 2024)
Index by Scopus